2012
DOI: 10.1071/he12086
|View full text |Cite
|
Sign up to set email alerts
|

Health Public Policy Public opinion on food-related obesity prevention policy initiatives

Abstract: Overall, these findings indicate that there is strong public support for the introduction of policy initiatives aimed at creating a healthier food environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
98
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 20 publications
12
98
0
Order By: Relevance
“…the taxation questions were preceded by the question "would you be in favour or against government taking the following actions to support healthy eating?"). 9 The finding that a tax was least supported aligned with other results that show that interventions that are less intrusive, such as those that provide information, are more acceptable than those that aim to discourage behaviours through disincentives such as taxation. 18 Similar to findings of a 2013 systematic review, our study also found that, generally, women and older people were more supportive of policy interventions than other groups.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…the taxation questions were preceded by the question "would you be in favour or against government taking the following actions to support healthy eating?"). 9 The finding that a tax was least supported aligned with other results that show that interventions that are less intrusive, such as those that provide information, are more acceptable than those that aim to discourage behaviours through disincentives such as taxation. 18 Similar to findings of a 2013 systematic review, our study also found that, generally, women and older people were more supportive of policy interventions than other groups.…”
Section: Discussionsupporting
confidence: 65%
“…17 Similarly, an Australia-wide study in 2010 found higher levels of support for a 'trafficlight' style of labelling (87%) and restrictions on advertising unhealthy food to children on television (83%) than taxing unhealthy foods and using the money for health programs (62%). 9 That study reported stronger support for increasing the price of unhealthy foods to reduce the cost of healthy foods (71%) than our study, although a direct comparison cannot be made because more contextual information was provided leading up to each question in the 2010 study (e.g. the taxation questions were preceded by the question "would you be in favour or against government taking the following actions to support healthy eating?").…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…taxation on energy-dense drinks and snacks, 63 while possibly subsidising healthier options, such as vegetables and fruit, which can prove economically prohibitive to those at the bottom of income scales 64 ii. banning advertising that aims to increase children's desire for low-nutrient, energy-dense food products [65][66][67] iii. discouraging sedentary behaviours such an excess of 'screen time' [68][69][70] and encouraging active participation in sport.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of respondents favoured approaches such as the provision of information on healthy choices, and just over half (53 %) agreed that the government should 'not get involved in what people choose to eat'. Population-based surveys in Denmark, Germany, Australia and the USA have also shown less public support for regulation and taxation (13)(14)(15)(16) . One explanation for the low support for more intensive government intervention may be the perceived causes of overweight and obesity (17) .…”
mentioning
confidence: 99%